The Association Between Believing in Free Will and Subjective Well-Being Is Confounded by a Sense of Personal Control - Gooding, Peter L. T.; Callan, Mitchell J.; Hughes, Gethin (Frontiers in Psychology, 2018)
The extent to which an individual believes in free will is associated with a number of positive life outcomes, including their own subjective well-being. However, it is not known whether the belief that one has free will per se is uniquely associated with subjective well-being over and above potential confounding variables. We examined a sense of personal control as one such confound—specifically, whether the association between free will belief and subjective well-being is based, in part, on the degree to which an individual feels a sense of personal control over their life. In Study, 1 trait-level belief in personal control significantly uniquely predicted satisfaction with life and stress, over and above the contribution of free will belief. In Study 2, within-person daily fluctuations in stress and depression were not significantly predicted by daily changes in free will belief over and above the contribution of personal control/choice. The findings provide new insight into the relationship between free will belief and subjective well-being.